Media Sosial Sebagai Sumber Berita Altenatif - Rahmatullah, Syukri; Dwi Yuliati, Retna Eni (Faculty of Da'wa and Communications Sciences, 2022)
Journalism is currently growing and developing with digital media. Digitization of journalism has penetrated into social media. Social media platforms on news can be used as news providers. Tiktok, Twitter, Facebook and Instagram are social media used in digital news. This study aims to determine the extent to which the role of social media Tiktok, Twitter, Facebook and Instagram is more accepted than conventional media in the news portals Kompas.com, Tempo.co and Republika.co.id. The online portals that are the object of research are Kompas.com, Tempo.co and Republika.co.id. This study uses a qualitative knife to dissect. The data collection technique in this study was the researcher observing the social media accounts of Kompas.com, Tempo.co and Republika.co.id. Furthermore, the researchers dig up information by interviewing the editors of Kompas.com, Tempo.co and Republika.co.id. The findings in this study conclude that Tiktok, Twitter, Facebook and Instagram are more accepted than conventional print media. The comment column is the most favorite thing for readers of the Kompas.com, Tempo.co and Republika.co.id portals on their respective social media. By using social media, it has the impact that the news is getting closer to the community, not at the exclusive level, but the news can be enjoyed egalitarianly.